Uncertainty in the conjunctive approach to fuzzy inference - Kudłacik, Przemysław (Zielona Góra: Uniwersytet Zielonogórski)
Fuzzy inference using the conjunctive approach is very popular in many practical applications. It is intuitive for engineers, simple to understand, and characterized by the lowest computational complexity. However, it leads to incorrect results in the cases when the relationship between a fact and a premise is undefined. This article analyses the problem thoroughly and provides several possible solutions.
Keywords: fuzzy inference; conjunctive approach; fuzzy truth value